Ethnomathematical Exploration of Garutan Batik Motifs - Sumartini, Tina Sri; Rahmawati, Restu (PRISMA, 2024)
Ethnomathematics provides benefits in linking mathematics with culture so that it can develop students' understanding of concepts. One culture that can be used is batik which has certain patterns and is philosophically related to mathematical concepts. The aim of this research is to explore mathematical concepts in Garutan batik and determine the value of mathematical philosophy in Garutan batik motifs. The research method used is qualitative with an ethnographic approach. The subjects of this research were batik craftsmen, batik managers of the Batik Garutan RM industry and mathematics teachers. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research are that in Garutan Batik there are mathematical concepts, namely geometric transformations in the form of translation, reflection and rotation. The merak ngibing batik motif is related to the concepts of translation and reflection. The bulu ayam batik motif is related to the concept of translation. The lereng kangkung batik motif is related to the concept of rotation and translation. The cupat manggu batik motif is related to the concepts of reflection, rotation and translation. The batik lereng batik motif is related to the concept of rotation and translation.